The Relationship between Learning Motivation and Biology Learning Outcomes of Grade XI Science Students at SMA Hidayatun Najah Proppo, Pamekasan - Maskur Rohman; Moch Haikal (Lombok Institute, 2025)
This study aimed to analyze the relationship between learning motivation and biology learning outcomes among Grade XI science students at SMA Hidayatun Najah Proppo, Pamekasan, within the implementation of a guided inquiry learning approach. The study employed a quantitative correlational design and involved 19 students from Class XI IPA 1 as the sample. Learning motivation was measured using an ARCS model (Attention, Relevance, Confidence, Satisfaction) questionnaire, while learning outcomes were assessed using an essay test on the coordination system topic. Data were analyzed using simple linear regression assisted by Jamovi software. The results showed that learning motivation was not significantly associated with biology learning outcomes (R = 0.0373; R^2 = 0.00139; F(1,17) = 0.0237; p = 0.880), explaining only 0.139% of the variance. These findings indicate that, in the context of a pesantren-based school with limited face-to-face instructional time and students’ dense activity schedules, learning outcomes are likely influenced more strongly by factors other than the motivation measured in this study. Accordingly, improving biology learning outcomes requires interventions that not only strengthen motivation but also optimize the learning environment, coordinate school–pesantren schedules, and enhance the quality of guided inquiry implementation so that students’ motivation can be effectively converted into optimal academic achievement.